Molière and the Age of Enlightenment - Wagner, M (Voltaire Foundation, 2017)
Introduction Chapter I. Molière and the eighteenth-century public at large Chapter II. General trends in Molière criticism in the first half of the eighteenth century Chapter III. Voltaire Chapter IV. Diderot and the encyclopedists Chapter V. Rousseau and the stage controversy Chapter VI. Last decades of the ancien régime, and Beaumarchais Conclusion List of works consulted